2017
DOI: 10.1371/journal.pone.0177322
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidative effects of 4-hydroxybenzyl alcohol in astrocytes confer protective effects in autocrine and paracrine manners

Abstract: 4-Hydroxybenzyl alcohol (4-HBA) is an important phenolic constituent of Gastrodia elata Blume (GEB), a traditional herbal medicine used in East Asia. Many activities have been reported to underlie the beneficial effects of 4-HBA in the brain, and in particular, its anti-inflammatory, anti-oxidative, and anti-zinc-toxic effects have been implicated in the postischemic brain. Here, the authors investigated the anti-oxidative effect of 4-HBA on astrocytes and sought to identify the underlying molecular mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Modern pharmacological studies have shown that RGE extract has neuroprotective, antioxidant, anti-anxiety, anti-depressant, sedative, anti-inflammatory and anti-angiogenic effects [4,5,6,7,8,9,10]. Gastrodin (GAS) and p -hydroxybenzyl alcohol (HBA) have been considered to be the active ingredients for a long time, due to their significant pharmacological activities [11,12,13,14,15]. Therefore, they were listed as the quality evaluation indicators of RGE in the Chinese Pharmacopoeia all along.…”
Section: Introductionmentioning
confidence: 99%
“…Modern pharmacological studies have shown that RGE extract has neuroprotective, antioxidant, anti-anxiety, anti-depressant, sedative, anti-inflammatory and anti-angiogenic effects [4,5,6,7,8,9,10]. Gastrodin (GAS) and p -hydroxybenzyl alcohol (HBA) have been considered to be the active ingredients for a long time, due to their significant pharmacological activities [11,12,13,14,15]. Therefore, they were listed as the quality evaluation indicators of RGE in the Chinese Pharmacopoeia all along.…”
Section: Introductionmentioning
confidence: 99%
“…4HYBZOH is a colourless liquid with a mild and pleasant scent with authorised used as food additive in restricted amounts by the "regulation (EU) No 872/2012 of 1 October 2012". It has been identified in small amounts in Arcangelisia gusanlung (a small shrub from China) and has little industrial use beyond the food industry, with specialty applications in the pharmaceutical (Luo et al, 2017) and materials (Tao et al, 2017) industries. Chlorinated benzyl alcohols have never, to the best of the author's knowledge, been reported to occur naturally, thus are exclusively anthropogenic.…”
Section: Benzyl Alcoholsmentioning
confidence: 99%
“…In addition, it can upregulate and can activate Nrf2 and consequently stimulate the expression of some antioxidative enzymes including HO‐1, NAD(P)H quinone dehydrogenase 1 (NQO1), and GCLM. Other signaling pathways such as extracellular signal‐regulated kinase (ERK) and Akt also were activated by gastrodigenin (Luo et al, ).…”
Section: Neurotoxicitymentioning
confidence: 99%